Determination of metallothionein at the femtomole level by constant current stripping chronopotentiometry - Kizek, R; Trnková, T L; Palecek, E (Analytical chemistry, 2001)
Metallothionein (MT) from rabbit liver was analyzed by differential pulse polarography, cyclic voltammetry, square wave voltammetry, and chronopotentiometric stripping analysis (CPSA) with a hanging mercury drop electrode under various conditions. The highest sensitivity of the MT determination was obtained with CPSA which produced a well-developed peak H due to catalytic hydrogen evolution at highly negative potentials. The highest peak H was obtained in borate buffer close to pH 8.0. In this medium, subnanomolar concentrations of MT were detectable. In the adsorptive transfer stripping (medium exchange) experiments, determination of few femtomoles of MT in 5-microL aliquots of the analyte was possible. CPSA determination of MT in various tissues of carp (Cyprinus carpio) yielded values in agreement with the published data.
Keywords: mikrochemie; játra; Polarography; Mercury; Animals; metalothionein; rtuť; potenciometrie; králíci; Electrodes; Liver; zvířata; Potentiometry; elektrody; polarografie; Metallothionein; Microchemistry; Rabbits